SAFETY, RISK, AND RELIABILITY OF CYBER NETWORK IN OIL AND GAS INDUSTRY - ONUNTUEI, Essang (PUPIL: International Journal of Teaching, Education and Learning, 2018)
As cyber network cuts across all works of life, several endemic dangers abound. Cyber theft and loss of resources to unauthorised persons has brought a grave concern to the public despite efforts to prevent its occurrence. So, the study considered the link between percentages of systems attacked and insiders’ cyber exploits; the impact of early threat detection on prompt response to cyber-attacks, and whether the percentage of systems attacked is a function of threat response duration and cyber welfare package in Nigeria’s major oil and gas firms as well. The methods of data analysis used include Pearson product moment correlation, Chi-square, and multiple regression analysis respectively. The results of findings show a link between the percentage of systems attacked and insiders’ cyber exploits in Nigeria’s major oil and gas firms; early threat detection impacting on prompt response to cyber-attacks, and percentage of systems attacked is a function of threat response duration and cyber welfare package respectively. Also, based on findings, recommendations were made on safety, risk, and reliability of cyber network in Nigeria’s oil and gas industry.